Pengaruh Kualitas Pelayanan,Lokasi, Dan Fasilitas Terhadap Keputusan Pembelian Diwarkop Labong - Imam Masduki; Marlina Siregar; Bhakty Helvi Rambe (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to answer the influence of service quality, location, and facilities on purchasing decisions at the Labong Rantauprapat coffee shop. Data collection was carried out by distributing questionnaires to 60 customers of the Labong Rantauprapat coffee shop. This study uses quantitative methods and performs data processing with IBM SPSS Statistics 26tools.This analysis includes reliability tests, validity tests, classical assumption tests, statistical tests,and multiple linear regression tests.The results of the t-test (partial) show that service quality has a positive and significant effect on purchasing decisions with a coefficient value of 0.772 with a probability value of 0.000 and a calculated t-value of 1.896. location has a positive and significant effect on purchasing decisions with a coefficient value of 0.406 with a probability value of 0.008 and a t-value of 1.759. Facilities have a positive and significant effect on purchasing decisions with a coefficient value of 0.017 with a probability value of 0.004 and a t-count value of 2.264 while the results of the F (simultaneous) test show a value of 3.233 which means that service quality, location, facilities together have a significant influence on purchasing decisions at the Labong Rantauprapat coffee shop.Multiple linear test results show Keywords: Service Quality, Location, Facilities,Purchase Decision